PERANCANGAN SISTEM APLIKASI MONITORING KEHADIRAN KARYAWAN BERBASIS MOBILE DAN GPS TRACKING BPJS KETENAGAKERJAAN KABUPATEN BANYUWANGI - Fariha Husnaini Widat (CV. Denasya Smart Publisher, 2025)
This study aims to design an employee attendance monitoring system based on a mobile application integrated with GPS tracking at BPJS Ketenagakerjaan Banyuwangi. The main issues in the previous attendance system include limited features, error-prone manual processes, and inefficiency in verifying attendance data. The research applies the prototype development method with both quantitative and qualitative approaches, involving interviews, surveys, observations, and application testing. The proposed system features real-time GPS-based attendance, online leave requests, automated notifications, and a reporting dashboard for management. The design results indicate that the system improves data accuracy, minimizes attendance fraud, and simplifies employee monitoring. Therefore, the application is expected to enhance human resource management more effectively, efficiently, and transparently.